2002
DOI: 10.5367/000000002101293831
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Rice for Tomorrow's Food Security: Can the Chinese Miracle be Replicated in Other Countries?

Abstract: The growth in rice production in Asia fell from 2.6% between 1966 and 1990 to 1.4% during the 1990s, mainly due to a deceleration in yield growth in the most intensively irrigated environments, where farm-level yields had already reached about 6.0 t ha-1. At this threshold of yields, farmers required more groundbreaking technology to elevate yields in highly productive environments. Inspired by the success of the 'Chinese miracle', policy makers and research managers in tropical Asia considered hybrid rice, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 6 publications
(6 reference statements)
4
24
0
Order By: Relevance
“…The NSB also does not monitor and supervise the performance of imported seed at farmers' fields. Exploiting this opportunity, private seed companies have imported more than 50 rice hybrids largely from China and India (Janaiah et al, 2002) to be sold to farmers at exorbitant prices for profit. Additionally farmers claimed that the outstanding amounts of imported seeds that are not sold in the current season are unscrupulously preserved for selling in the following season ignoring the deterioration of germination percentage and its consequential impact.…”
Section: An Item-wise Analysis Of Risk As Perceived By Farmersmentioning
confidence: 99%
See 1 more Smart Citation
“…The NSB also does not monitor and supervise the performance of imported seed at farmers' fields. Exploiting this opportunity, private seed companies have imported more than 50 rice hybrids largely from China and India (Janaiah et al, 2002) to be sold to farmers at exorbitant prices for profit. Additionally farmers claimed that the outstanding amounts of imported seeds that are not sold in the current season are unscrupulously preserved for selling in the following season ignoring the deterioration of germination percentage and its consequential impact.…”
Section: An Item-wise Analysis Of Risk As Perceived By Farmersmentioning
confidence: 99%
“…Continuing adopters still continue cultivating hybrid rice because of possessing larger farms and having higher family incomes. Janaiah, Hossain, & Husain (2002) conducted a study on hybrid rice in India and Bangladesh and reported that higher risk in cultivating hybrid rice is one of key issues for farmers (as indicated by about 80% of respondents). But the actual risk occurrence is not ubiquitous; rather it is area specific.…”
Section: Findings 31mentioning
confidence: 99%
“…The only drawback with hybrid technology comprised of hybrid vigour along with other desired traits lost due to genetic segregations in subsequent generation. Moreover, the cost of seed and new seed for every sowing are the big challenges faced by subsistence farmers [60]. The preservation of hybrid seed qualities had significant implication to ensure food security, environmental preservation and employment.…”
Section: Synthetic Apomixis Through Genome Editing To Preserve Hybridmentioning
confidence: 99%
“…Adoptions of hybrid rice have remained low in SEA countries. While its share had increased in China from 15% in the early 1980s to 50% in early 1990s, and 60% in the 2010s (Janaiah et al 2002;Spielman et al 2012), its adoption rate had remained around 10% in Viet Nam, 7% in Bangladesh, and 5% in the Philippines, Indonesia, as of 2010 (Spielman et al 2012;FAO 2018).…”
Section: Improved Varietiesmentioning
confidence: 99%